The effects of TerraZyme on the shear strength of soils - Juinio, Mark Ivan R.; Valdez, Gideon L.
The study aims to determine the effects of TerraZyme on the shear strength of soils such as CE Soil (or Silty Sand) and Vermicast. Its main objective is to compare the TerraZyme treated soils with the untreated ones. It also seeks to determine the role of curing time and variability of soils used in treatment applied. TerraZyme is intended for the improvement on soils beneath the roads. To accomplish the objectives, soil characterization and Direct Shear Test were conducted. The concentration to be used was 1% while the curing times were 1 week, 2 weeks and 4 weeks. The normal pressures applied on the direct shear were 18, 36, and 72 kilograms in order to define shear strength parameters cohesion, c, and angle of friction, Փ. The direct shear conformed to ASTM D3080-11. In the end, the degree of effectively of TerraZyme to the shear strength of soil was presented. The effects of curing time were also analyzed. Based on the obtained results, the CE Soil improved its suitability in road construction after treatment of TerraZyme since an increase from A-2-6 to A-2-4 using AASHTO Soil Classification System was observed. The Vermicast, on the other hand, showed no improvements after treatment and remained as organic soils. Furthermore, based on the results of the direct shear test conducted, it showed that application of TerraZyme and prolonged curing are beneficial in terms of shear strength for Vermicast and not on CE Soil. For further comparison, changes in peak shear stress, cohesion and angle of friction were compared individually for the treatment and curing time to check the effects of TerraZyme on the individual shear strength parameters of both soils.